1998
DOI: 10.1046/j.1460-9568.1998.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Ca2+ and Na+ channels on mouse Schwann cells cultured in serum‐free medium: regulation by a diffusible factor from neurons and by cAMP

Abstract: Regulation of expression of functional voltage-gated ion channels for inward currents was studied in Schwann cells in organotypic cultures of dorsal root ganglia from E19 mouse embryos maintained in serum-free medium. Of the Schwann cells that did not contact axons, 46.5% expressed T-type Ca2+ conductances (ICaT). Two days or more after excision of the ganglia, and consequent disappearance of neurites, ICaT were detectable in only 10.9% of the cells, and the marker 04 disappeared. On Schwann cells deprived of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
1
4
0
1
Order By: Relevance
“…The partial antagonistic action of H89 above 0.3 μ m could be due to unspecific effects of the PKA inhibitor that at higher concentrations may inhibit various kinases (Davies et al 2000). Our data are in good agreement with previous reports showing that a cAMP‐dependent pathway is involved in the recruitment of T‐type channels in Schwann and neuroendocrine cells (Beaudu‐Lange et al 1998; Mariot et al 2002), although both reports do not mention the existence of PKA‐dependent or PKA‐independent pathways. A PKA‐independent down‐regulation of the α6 subunit of GABA A receptors in mature rat cerebellar granule cells has also been shown (Thompson et al 2000).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The partial antagonistic action of H89 above 0.3 μ m could be due to unspecific effects of the PKA inhibitor that at higher concentrations may inhibit various kinases (Davies et al 2000). Our data are in good agreement with previous reports showing that a cAMP‐dependent pathway is involved in the recruitment of T‐type channels in Schwann and neuroendocrine cells (Beaudu‐Lange et al 1998; Mariot et al 2002), although both reports do not mention the existence of PKA‐dependent or PKA‐independent pathways. A PKA‐independent down‐regulation of the α6 subunit of GABA A receptors in mature rat cerebellar granule cells has also been shown (Thompson et al 2000).…”
Section: Discussionsupporting
confidence: 93%
“…Cells were plated on plastic dishes pretreated with poly‐ l ‐ornithine (1 mg ml −1 ) and laminin (5 μg ml −1 in L‐15 carbonate), incubated at 37°C in a water‐saturated atmosphere with 5% CO 2 and used within 2–6 days of plating. The culture medium was made serum‐free to prevent different batches from inducing different effects on the recruitment of T‐type channels (see Beaudu‐Lange et al 1998). The medium contained: Dulbecco's modified Eagle's medium (DMEM), penicillin–streptomycin 0.5% and gentamycin 0.25%, and was not changed during the culture period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schwann cells were cultured from excised dorsal root ganglia from OF1 mouse embryos (E19) as previously described (Amédée et al ., 1991; Beaudu‐Lange et al ., 1998). Mice were killed by decapitation.…”
Section: Methodsmentioning
confidence: 99%
“…Boudier, unpublished results) that could be accounted for by an increase in the number of Schwann cells and the extension of Schwann cell processes (Lubischer and Thompson, 1999). Previous studies have already reported the presence of tetrodotoxin‐sensitive sodium currents in Schwann cell cultures derived from rabbit, rat, and frog sciatic nerves (Shrager et al, 1985; Miyazaki et al, 1994), or from mouse dorsal root ganglia (Beaudu‐Lange et al, 1998). Using excised patches, Chiu (1993) recorded sodium currents in freshly isolated Schwann cells from 10‐week‐old rabbit sciatic nerve.…”
Section: Discussionmentioning
confidence: 98%